The application of bacteriophage to veterinary and One-Health medicine—a road map - Atterbury, Robert J.; Gigante, Adriano M.; Jalasvuori, Matti; Lavigne, Robert; Schouler, Catherine; Mariano, Valeria; Barrow, Paul (Frontiers in Microbiology, 2026)
The STAR-IDAZ international research consortium established a working group on Alternatives to Antimicrobials to explore various approaches for reducing our reliance on antimicrobials. These included bacteriophages, activating the immune system and manipulating the microbiome. The sub-group investigating bacteriophages have developed a road map for the application of phages in a One Health context. We present this roadmap here, in review format, along with a discussion of how phages may be combined with other therapies.